Characterization of PlyB221 and PlyP32, Two Novel Endolysins Encoded by Phages Preying on the Bacillus cereus Group - Audrey Leprince; Manon Nuytten; Annika Gillis; Jacques Mahillon (Viruses, 2020)
Endolysins are phage-encoded enzymes implicated in the breaching of the bacterial cell wall at the end of the viral cycle. This study focuses on the endolysins of Deep-Blue (PlyB221) and Deep-Purple (PlyP32), two phages preying on the Bacillus cereus group. Both enzymes exhibit a typical modular organization with an enzymatically active domain (EAD) located in the N-terminal and a cell wall binding domain (CBD) in the C-terminal part of the protein. In silico analysis indicated that the EAD domains of PlyB221 and PlyP32 are endowed with peptidase and muramidase activities, respectively, whereas in both proteins SH3 domains are involved in the CBD. To evaluate their antimicrobial properties and binding specificity, both endolysins were expressed and purified. PlyB221 and PlyP32 efficiently recognized and lysed all the tested strains from the B. cereus group. Biochemical characterization showed that PlyB221 activity was stable under a wide range of pHs (5–9), NaCl concentrations (up to 200 mM), and temperature treatments (up to 50 °C). Although PlyP32 activity was less stable than that of PlyB221, the endolysin displayed high activity at pH 6–7, NaCl concentration up to 100 mM and the temperature treatment up to 45 °C. Overall, PlyB221 and PlyP32 display suitable characteristics for the development of biocontrol and detection tools.